Advances in Experimental Medicine and Biology
DOI: 10.1007/0-387-24980-x_6
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide and Glycidamide: Approach towards Risk Assessment Based on Biomarker Guided Dosimetry of Genotoxic/Mutagenic Effects in Human Blood

Abstract: Acrylamide (AA) is a carcinogen as demonstrated in animal experiments, but the relevance for the human situation is still unclear. AA and its metabolite glycidamide (GA) react with nucleophilic regions in biomolecules. However, whereas AA and GA react with proteins, DNA adducts are exclusively formed by GA under conditions simulating in vivo situations. For risk assessment it is of particular interest to elucidate whether AA or GA within the plasma concentration range resulting from food intake are "quenched" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Acrylamide is metabolized very fast after ingestion and then is going into blood and urine from where it is excreted. Most critical for the genotoxic effect of acrylamide is the epoxidation of acrylamide to glycidamide by Cytochrome P450, a hemoprotein with enzyme activity . Glycidamide can react with hemoglobin and enzymes but also with DNA resulting in point mutations and cancer.…”
Section: Toxicitymentioning
confidence: 99%
“…Acrylamide is metabolized very fast after ingestion and then is going into blood and urine from where it is excreted. Most critical for the genotoxic effect of acrylamide is the epoxidation of acrylamide to glycidamide by Cytochrome P450, a hemoprotein with enzyme activity . Glycidamide can react with hemoglobin and enzymes but also with DNA resulting in point mutations and cancer.…”
Section: Toxicitymentioning
confidence: 99%
“…Metabolic formation of glycidamide is essential for genotoxic effectiveness. 24 Thus, glycidamide acts like the ultimate genotoxic metabolite of acrylamide and it was found to form DNA adducts (from N 7 of guanine or N 3 of adenine) and induce micronuclei in different organs of mice. [25][26][27] Acrylamide is a well-recognized potent neurotoxin affecting both the central nervous system (CNS) and peripheral nervous system (PNS).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the current research on patients' diet have shown that the consumption of bread, cereal and meat food groups was lower compared with standard serving sizes for dietary groups. There are many studies which have shown the effects of diet on the development of ovarian cysts or other female reproductive disorders [6]- [9]. There is also a significant relationship between diet and polycystic ovarian syndrome [16], [17] and between diet and seromucinous benign ovarian cysts development [18].…”
Section: Discussionmentioning
confidence: 99%
“…Diet has a significant part in development of several female physiological or clinical disturbances. Infertility or abortion is most common complications caused by Acryl amide consumption [6]. Studies have shown that the saturated lipids in egg or meet can lead to painful menstruation [7].…”
Section: Introductionmentioning
confidence: 99%